Path Planning of Multi-Robot System Based on Tracking of External Stimuli - Kheerallah, Yousif Abdulwahab; Rashid, Mofeed Turky; Rashid, Abdulmuttalib Turky; Marhoon, Ali Fadhil (Discontinuity, Nonlinearity, and Complexity, 2026)
In designing a leader-follower system, the main challenge is how to distinguish the leader among other moving robots. In this paper, a multi robot system will be designed in which the robots are attracting to a spotlight as their leader. This behavior is inspired from the collective motion of the Artemia aggregations. Two dynamical models will be designed based on the newton equation and its parameters can be estimated by two methods: first, depending on the physical feature of the robots, second, the using the least square estimation method. The performance of the proposed systems will be tested by: tracking the spotlight path, achieving formation and avoiding obstacles depending on the virtual circle method. For this purpose, several experiment will be implemented, which may be divided into two scenarios: without and with obstacles. Each scenario has three type of experiments, depending on the spotlight path, such as the straight, circle and zigzag path experiment. These tests will be implemented within the V-REP simulator and the results of the tests show perfect behavior of the robots during the path tracking and the obstacles avoiding.